IJRBAT 2018
DOI: 10.29369/ijrbat.2018.01.i.0074
|View full text |Cite
|
Sign up to set email alerts
|

Various Types of Rudraksha Beads, Their Benefits and Ftir Spectra

Abstract: The word rudraksha, originated from two Sanskrit words Rudra & Aksha, (Rudra means Lord Shiva, Aksha means Eye). The rudraksha bead is the dried fruit of the tree Elaeocarpus Ganitrus. Rudraksha farming is a difficult process due to the slow sprouting from the beads. Depending on the humidity of the soil, it usually takes 1-2 years for a tree to sprout. Rudraksha is grown in subtropical climatic regions with temperature ranges of 25-30 degree centigrade. The tree starts giving fruit after 7 years. A single Rud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
3
2
0
1
Order By: Relevance
“…Additionally, the XRD results supported an EA that determined the rudraksha's composition to be C (48.46%), H 2 (6.37%), N (0.54%), S (0.08%), and O 2 (44.5%). According to data reported by Gupta (2018), rudraksha has a chemical composition of 50.031% C, 0.95% N, 17.897% H, and 30.53% O 44 . This study demonstrated that the chemical compositions of C, H, N, and S are found to be slightly lower than the prior data.…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…Additionally, the XRD results supported an EA that determined the rudraksha's composition to be C (48.46%), H 2 (6.37%), N (0.54%), S (0.08%), and O 2 (44.5%). According to data reported by Gupta (2018), rudraksha has a chemical composition of 50.031% C, 0.95% N, 17.897% H, and 30.53% O 44 . This study demonstrated that the chemical compositions of C, H, N, and S are found to be slightly lower than the prior data.…”
Section: Resultssupporting
confidence: 49%
“…The peak levels of the spectrum for pure rudraksha filler were observed at 2916 cm À1 and 2853 cm À1 . Previous studies also reported that sharp and strong intensities of varying functional groups, including alkane, methyl, methylene, ethyl, and alkene, were found in a similar spectrum band to that of rudraksha, at 2925.28 cm À1 and 2854.35 cm À1 , respectively (Gupta, 2018). Identical characteristics were discovered for epoxy and rudraksha composites made with various concentration loadings.…”
Section: Fourier-transform Infrared Spectroscopysupporting
confidence: 56%
See 2 more Smart Citations
“…La cáscara está constituida principalmente por celulosa, hemicelulosa y lignina, las cuales la hacen no comestible para los humanos, pero potencialmente aprovechable para obtener otros productos de valor agregado (Swaroopa y Krishna, 2004).…”
unclassified